Successful Crowdfunding in Indonesia Based on Financial Projection and Investor Attraction: Empirical Study on Micro, Small and Medium Enterprises (MSMEs) on the Bizhare Platform - Anggrian Faulina Permatasari; Ihyaul Ulum; Ike Arisanti (Universitas Muhammadiyah Yogyakarta, Indonesia, 2022)
Research aims: This study aims to examine the effects of investor attraction and financial projection on successful crowdfunding. Design/Methodology/Approach: A purposive sampling method was used by the researchers. The research sample consisted of 48 projects from the Bizhare platform from 2018 to 2021, with the following criteria: providing data that could be used as an indicator for measuring each variable. In testing the hypotheses, multiple linear regression analysis was employed with a principal component analysis model.Research Findings: The financial projection positively affected successful crowdfunding, while investor attraction negatively affected successful crowdfunding in Indonesia.Theoretical contribution/Originality: This study’s results are an additional discussion toward theory and literature related to crowdfunding.Practitioner/Policy implication: Disclosure of prospectus plays an essential role in preventing information asymmetry that may arise between managers and investors by providing knowledge to external investors. This study is needed to accelerate economic recovery due to the pandemic, which especially causes new projects to be trapped, saves MSMEs from limited capital, and improves business development.Research limitation/Implication: This research only used one platform as an object because not all crowdfunding platforms could be accessed and provided the information needed for research.